Pengelolaan Keuangan Daerah Melalui Penerapan SIPD di Kecamatan Pahandut Kota Palangka Raya Kalimantan Tengah - Sela, Zaneta Nathania Mei; Utomo, Decky Dwi; Ardieansyah, Ardieansyah (Innovative: Journal Of Social Science Research, 2025)
Regional financial management is essential to achieving good governance. In the digital era, the Regional Government Information System (SIPD) was developed to enhance transparency, accountability, and efficiency in budget management. Previous studies show that SIPD positively affects financial report quality, but its success depends on human resources and infrastructure readiness. This report, based on research in Pahandut Subdistrict, illustrates the practical application of SIPD in local financial operations. Findings highlight the importance of system integration and cross-functional competence for effective financial governance.